Pemahaman Hadis Kontemporer Yusuf Al-Qardhawi Dan Muhammad Al- Ghazali - Wafiq Mayada; Siti Ardianti; Abdul Ghoni; Andri Gunawan; Oky Akmal Rustandi; Maulana Halim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Hadith is anything in the form of words, actions, tacit approval, or characteristics (self-description) that is attributed to the Prophet Muhammad. What is meant by the nature (self-description) of the Prophet in this definition is the physical description and morals of the Prophet as reported by the narrators, such as his body being strong, his chest broad, he was a polite person and so on. Muhammad al-Ghazali was a famous scholar who was born in al-Buhairah, Egypt, precisely in Nakla Inab, a village which gave birth to many prominent Islamic figures of his time such as Muhammad 'Abduh, Mahmud Syaltut, Hasan alBana and Muhammad al-Madani, Yusuf Al -Qardhawi. He was born in the village of Shaft Turab in the middle of the Nile River Delta, Mahallah al-Kubra area, he already memorized the Koran. Completing his education at Ma'had Thantha and Ma'had Tsanawi, Qaradawi continued on to al-Azhar University, Cairo, Egypt, at the Ushuluddin Faculty, majoring in religious studies and graduating in 1952 where he received the shahadah 'aliyah. Then he continued his Arabic language studies for two years and graduated with the best achievement among five hundred students. These people have an understanding of hadith, then in this research we discuss the Understanding of Contemporary Hadith According to Yusuf Al-Qardhawi and Al-Ghazali. In this research, the qualitative approach used by researchers is library research, namely. activities related to library data collection methods. In terms of Hadith material, according to Yusuf Al-Qardhawi and Muhammad Ghazali: Related to current problems. As an effort to reinterpret the hadith in accordance with the current context.